Human Papilloma Virus as a risk factor for Carcinoma of Cervix: The Gynae Practitioners' View - Fareh, Shayela; Karim, Mohoshina (Ibrahim Cardiac Medical Journal, 2013)
Ibrahim Cardiac Medical Journal 2011; 1(2): 50-55 DOI: http://dx.doi.org/10.3329/icmj.v1i2.13561